(untitled) (Global Journal of Medical Research, 2020)
Introduction: Ovarian hyperstimulation syndrome (OHSS) is a rare, life-threatening serious complication of ovulation induction with human chorionic gonadotropin (hCG). (4) 3% of patients undergoing IVF (in vitro fertilisation) develop OHSS. But radiologically evident pleural effusions develop only in 1% among which hemorrhagic effusions are very rare (1) Pleural effusions due to OHSS are usually associated with ascites. Isolated unilateral pleural effusions are uncommon. (2,3) The syndrome occurs in the luteal phase or during early part of pregnancy. The syndrome was first described in 1941 and the first fatal case of OHSS with renal failure and death was described in 1951. The number of patients who undergo infertility treatment at IVF centers has been increasing.(2)Therefore, it should be kept in mind that there may be unilateral pleural effusion without peritoneal fluid in OHSS which can be life threatening and needs to be evaluated as soon as possible. Physicians should consider this potentially life-threatening diagnosis in all patients who undergo ovarian hyperstimulation. (4) Here, we present a case with ISOLATED UNILATERAL HEMORRHAGIC PLEURAL EFFUSION due to OHSS.